Pulse Of Amendment Of Article 7 Of The 1945 Constitution During The Covid-19 Pandemic In Indonesia - Dony Yusra Pebrianto; Sabri Yanto; Yanita Kusuma (Eduvest - Journal of Universal Studies, 2021)
The issue of the amendment of article 7 of the 1945 Constitution in Indonesia has caused an uproar among the public during the COVID 19 pandemic. Although constitutionally amendments can be made as article 37 of the 1945 Constitution, it needs to be seen from three sections, namely: 1. Changing the constitution with careful consideration, not carelessness and self-awareness; 2. Give people the opportunity to express their views before making changes; 3. Protect the rights of individuals or minorities. The results of several survey institutions in Indonesia amendments to the three-term presidential term some Indonesians refused. The purpose of this study is to provide a scientific foundation on the pulse rate of the 1945 Constitution during the current COVID-19 pandemic in Indonesia. The purpose of this study is to provide a scientific foundation on the pulse rate of the 1945 Constitution during the current COVID-19 pandemic in Indonesia. The study uses normative legal methods, using three methods, namely: legal methods, historical methods, and conceptual methods. The recommendation of this study is to provide advice and input to JokPro groups and government support parties in the discourse of the idea of a three-term president related to article 7 of the 1945 Constitution